Coronavirus Infection in a Child of the First Year of Life: a Case Report - Nailya R. Hafizova; Dinara R. Merzlyakova; Natalia A. Druzhinina; Galina P. Shiryaeva; Tatiana B. Khayretdinova; Liliya R. Imaeva; Gulnaz A. Vakhitova; Aliya R. Khabibullina; Alfiya I. Nazarova (Вестник восстановительной медицины, 2023)
INTRODUCTION. Over the past few months, the topic of multisystem inflammatory syndrome in children has been evolving at anextraordinary pace, as evidenced by the increasing number of publications on this subject. The disease does not begin to developimmediately, not at the moment the virus enters the body, but after some time, and that is 14-21 days later. This is evidenced by thepresence of IgG antibodies and the absence of RNA virus in the biological loci. Representatives of the Pediatric Intensive Care Society ofGreat Britain felt it necessary to circulate the “PICS Statement”, which contained data on the increasing number of children with a newmultisystem inflammatory disease associated with positive tests for SARS-CoV-2. However, it should be noted that this associationwas confirmed in only some patients by appropriate tests performed in laboratory settings. The course of the disease was similar toa toxic shock syndrome and atypical Kawasaki disease, for which the characteristic symptoms are heart disease, abdominal pain andgastrointestinal symptoms. The patients showed abnormalities in blood parameters, changes in the number of blood corpuscules, thelevel of C-reactive protein (CRP), ferritin, troponin, brain natriuretic propeptide (NT-proBNP) was high.AIM. Using a case study to show the importance of a timely detection, treatment and follow-up of children with a new coronavirusinfection.MATERIAL AND METHODS. The mother of a 3-month-old child (the subject of the study) applied to the follow-up office of theRepublican Children’s Clinical Hospital in Ufa with a history of COVID-19 infection. The following were used to diagnose the currentcondition: copying of data from medical records, clinical examination with assessment of physical and psychomotor development,consultations of single-skilled specialists to make a diagnosis, laboratory and instrumental examinations.RESULTS AND DISCUSSION. The article presents an observation of a 1-year-old patient with COVID-19 infection complicatedby multisystem inflammatory syndrome, including the Kawasaki syndrome. In this patient, against the background of the thirdhospitalization for COVID-19, a positive dynamics of the course of the disease was achieved with discharge to the outpatient stage oftreatment and follow-up.CONCLUSION. Lesions of organs and organ systems caused by COVID-19 require an integrated approach to diagnosis and managementof patients. Further accumulation of data on diagnosis and clinical course of the new coronavirus infection in children remains an urgentscientific and practical task.